Water balance and locomotor performance in three species of neotropical toads that differ in geographical distribution - Titon, Braz [UNESP]; Navas, Carlos Arturo; Jim, Jorge [UNESP]; Gomes, Fernando Ribeiro [UNESP] (Elsevier B.V., 2010)
Water availability in the environment is a fundamental factor in determining the limits of geographical distribution and the evolution of the physiological characters associated to water balance in anurans. In this paper, we compare some aspects of water balance and the sensitivity of locomotor performance to dehydration at different temperatures for three species of toads from the genus Rhinella, with different levels of dependence on forested environments. Results show patterns associated to interspecific differences in both geographical distribution and time of seasonal reproduction. Sensitivity of locomotor performance to dehydration was lower at low temperatures for R. icterica, the species that are reproductively active during winter and lower at intermediate temperatures for R. schneideri, the species that reproduces mostly during spring, suggesting a pattern of thermal adaptation of locomotor performance for these species. Otherwise. R. ornate, a species with broader reproductive season, shows high sensitivity of locomotor performance to dehydration at all temperatures tested, suggesting a stronger relation of breeding activity with patterns of rainfall than temperature variation. Furthermore, the low rates of water uptake of R. ornata may pose restrictions on the occupation of open areas by this species. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Anura; Dehydration effects; Evaporative water loss; Jumping ability; Water uptake